2002
DOI: 10.1016/s0886-3350(01)01227-5
|View full text |Cite
|
Sign up to set email alerts
|

Depth and age-dependent distribution of keratocytes in healthy human corneas

Abstract: In healthy living corneas, the keratocyte density was high in the areas adjacent to Bowman's and Descemet's membranes and was lower in patients older than 50 years than in those younger than 50 years. Further studies are needed to document the rate of change with age and to better understand the role and capacity of aging keratocytes in regenerative processes following corneal diseases or surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 18 publications
4
41
0
3
Order By: Relevance
“…2D); therefore a concentration of 12.5 million cells ml −1 was chosen for all further encapsulations. This value falls in the range of reported in vivo keratocyte densities [21].…”
Section: Hydrogel Culturessupporting
confidence: 68%
“…2D); therefore a concentration of 12.5 million cells ml −1 was chosen for all further encapsulations. This value falls in the range of reported in vivo keratocyte densities [21].…”
Section: Hydrogel Culturessupporting
confidence: 68%
“…[58][59][60][61][62] Keratoctye density, in addition, has been reported to decrease with increasing age, 60,62,64 however, other authors 57,63 have reported consistency in the corneal keratocyte populations throughout life. In this study, reduction in keratocyte density with age was found to be significant in the posterior stroma only, with a strong trend within the anterior stroma.…”
Section: 39mentioning
confidence: 99%
“…Several ocular surface agerelated changes have been reported in the literature such as [3] reduction in lacrimal secretion and changes on its composition [4]; reduction in functional meibomian glands and changes in lipid secretions [5]; the composition and amount of the tear film changes [6] and the conjunctival development of conjunctivochalasis [7]. Furthermore, the corneal sensitivity is reduced, epithelial and endothelial basement membranes increase its thickness, the number of keratocytes decrease [8] and there is an increased loss of corneal endothelial cells [9]. The incidence and prevalence of ocular diseases as age-related maculopathy, liquefaction of the vitreous, glaucoma, vascular occlusive diseases, cataract and dry eye increase significantly with age [10,11].…”
Section: Introductionmentioning
confidence: 99%